A Bibliometric Analysis of Qur’anic Learning Research in Scopus (1994–2024): Trends, Thematic Shifts, and Institutional Disparities - Nilna Fadlillah; Ni'matus Sholihah; Ah. Zakki Fuad; Mokhamad Syaifudin; Moh. Abdullah (AT-TA'LIM, 2025)
This study presents a bibliometric analysis of Qur’anic learning research, including teaching, learning, and memorization, indexed in Scopus from 1994 to 2024. A total of 120 journal articles and conference papers were examined using descriptive statistics and bibliometric mapping to identify publication trends, influential works, and thematic shifts within the field. The results indicate a steady growth in Qur’anic learning research over the past three decades, with a significant increase after 2009 and a peak in 2021. Indonesia and Malaysia emerge as the most prominent contributors, reflecting strong institutional engagement in Qur’anic education research. The thematic analysis reveals a gradual shift from traditional pedagogical approaches toward more innovative and technology-assisted learning models, including multimedia applications and mobile-based memorization tools. While this study offers a systematic overview of internationally visible research outputs, it also acknowledges a methodological limitation, as reliance on Scopus-indexed publications may overlook a substantial body of unpublished or locally indexed research, particularly within Islamic higher education institutions (PTKI). A notable finding is the disparity in research intensity between general universities (PTU) and PTKI, indicating the influence of structural and policy-related factors on the development of Qur’anic learning research. Overall, this study provides insights for strengthening future research directions and institutional policies related to Qur’anic education.